DEPRESSION MEDIATES THE RELATION OF INSOMNIA SEVERITY WITH SUICIDE RISK IN THREE CLINICAL SAMPLES OF U.S. MILITARY PERSONNEL. Issue 9 (5th June 2015) - Bryan, Craig J.; Gonzales, Jacqueline; Rudd, M. David; Bryan, AnnaBelle O.; Clemans, Tracy A.; Ray‐Sannerud, Bobbie; Wertenberger, Evelyn; Leeson, Bruce; Heron, Elizabeth A.; Morrow, Chad E.; Etienne, Neysa
Abstract : Background: A growing body of empirical research suggests insomnia severity is directly related to suicide ideation, attempts, and death in nonmilitary samples, even when controlling for depression and other suicide risk factors. Few studies have explored this relationship in U.S. military personnel. Methods: The present study entailed secondary data analyses examining the associations of insomnia severity with suicide ideation and attempts in three clinical samples: Air Force psychiatric outpatients ( n = 158), recently discharged Army psychiatric inpatients ( n = 168), and Army psychiatric outpatients ( n = 54). Participants completed the Beck Scale for Suicide Ideation, the Beck Depression Inventory‐II or Patient Health Questionnaire‐9, the Insomnia Severity Index, and the Posttraumatic Stress Disorder Checklist at baseline; two samples also completed these measures during follow‐up. Results: Sleep disturbance was associated with concurrent (β's > 0.21; P 's < 0.059) and prospective (β's > 0.39; P 's < 0.001) suicide ideation in all three samples. When adjusting for age, gender, depression, and posttraumatic stress, insomnia severity was no longer directly associated with suicide ideation either concurrently (β's < 0.19; P 's > 0.200) or prospectively (β's < 0.26; P 's > 0.063), but depression was (β's > 0.22; P 's < 0.012). Results of a latent difference score mediation model indicated that depression mediated the relation of insomnia severity with suicide ideation. Conclusions: Across three clinical samples of military personnel, depression explained the relationship between insomnia severity and suicide risk.